Analisis Kontrastif Penanda Imperatif dalam Bahasa Jawa dan Bahasa Indonesia - Badriyah Wulandari (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2017)
This research describes and explains the similarities and differences of imperative signs in Javanese and Bahasa Indonesia. This is a descriptive qualitative research with content analysis. This research compares the imperative signs of Javanese and Bahasa Indonesia in morphological aspects of lexical and syntax. The result of this research shows that both lexical categories were signed by the use of affirmative and negative commands. In morphological category, imperative sentences both Javanese and Bahasa Indonesia were signed by affixes. Meanwhile, in syntax category, the imperative sentences were signed by phrases.Keywords : constranstive, imperative, Javanese, Bahasa indonesia